2024
DOI: 10.3847/1538-4365/ad0e0c
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Photospheric to Coronal Plasma Using Magnetohydrodynamic Characteristics. I. Data-driven Boundary Conditions

Lucas A. Tarr,
N. Dylan Kee,
Mark G. Linton
et al.

Abstract: We develop a general description of how information propagates through a magnetohydrodynamic (MHD) system based on the method of characteristics and use that to formulate numerical boundary conditions that are intrinsically consistent with the MHD equations. Our formulation includes two major advances for simulations of the Sun. First, we derive data-driven boundary conditions that optimally match the state of the plasma inferred from a time series of observations of a boundary (e.g., the solar photosphere). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 105 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…Indeed, such a description forms the basis of many numerical MHD methods (Harten et al 1983), and a (linear) version has been used to identify waves in solar wind observations (Zank et al 2023). Recently, Tarr et al (2024) demonstrated how the characteristic description of MHD could be used to locally decompose and reconstruct the dynamical evolution of an MHD system in terms of these fully nonlinear characteristic modes. While those authors focused on using the formalism to properly implement BCs, they suggested that the method is underutilized for the analysis of simulations, particularly for the unsolved problem of tracking the propagation and interaction of MHD waves in simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such a description forms the basis of many numerical MHD methods (Harten et al 1983), and a (linear) version has been used to identify waves in solar wind observations (Zank et al 2023). Recently, Tarr et al (2024) demonstrated how the characteristic description of MHD could be used to locally decompose and reconstruct the dynamical evolution of an MHD system in terms of these fully nonlinear characteristic modes. While those authors focused on using the formalism to properly implement BCs, they suggested that the method is underutilized for the analysis of simulations, particularly for the unsolved problem of tracking the propagation and interaction of MHD waves in simulations.…”
Section: Introductionmentioning
confidence: 99%